Cancer comorbidity in patients with non-obstructive coronary artery disease: Depressive symptoms related to C-reactive protein - Dounya Schoormans; Jos W. Widdershoven; Paula M.C. Mommersteeg (Brain, Behavior, & Immunity - Health, 2020)
Background: Based on guidelines for cardiovascular risk assessment among non-cancer populations, depression and anxiety can be seen as risk factors for CVD, on top of cardiotoxic cancer treatment and traditional CVD risk factors among cancer survivors. Increased inflammation can be a shared potential pathophysiological mechanism, as higher levels of inflammation (like C-reactive protein, CRP) are known associates of depression and anxiety. In turn, increased inflammation is involved in the pathogenesis of CVDs. Furthermore, both cancer and cancer treatment including chemotherapy and radiation can lead to elevated levels of inflammation. We will therefore examine whether the relation between depression and anxiety with inflammatory markers among patients with either CVD or cancer is different from those with both conditions. Method: The TweeSteden Mild Stenosis (TWIST) study among patients with non-obstructive coronary artery disease (NOCAD, luminal narrowing <60%), a type of ischemic heart disease, previously reported a significant association between depressive symptoms and increased inflammation (measured by high-sensitive (hs)CRP). Of the included NOCAD-patients, 6% had a history of cancer. The TWIST patient sample was therefore used to explore whether the association between depression and elevated inflammation (hsCRP) was similar for NOCAD-patients with and without a history of cancer. Results: The association between depressive symptoms and increased hsCRP levels is stronger among NOCAD-patients with a history of cancer than among NOCAD-patients without a history of cancer. Furthermore, whereas this relation is mediated by lifestyle factors among NOCAD-patients without cancer, the association remained significant after adjusting for BMI, smoking, and physical activity among NOCAD-patients with a history of cancer. Conclusion: The stronger association between depression and hsCRP among NOCAD-patients with a history of cancer indicates that there may be an additive or synergistic effect of having NOCAD and cancer for general inflammation and possibly depression.